Upah dan Etos Kerja pada Kasus Usaha Songket Palembang dalam Perspektif Islam dan Melayu - Antoni Antoni (Medina-te : Jurnal Studi Islam, 2018)
This research entitled "Wages and Working Ethics on Business Cases of Palembang Songket in Islamic and Malay Perspective", (1) the overview of Palembang songket effort during Sriwijaya and the Sultanate of songket craft has not become an economically valuable commodity since independence until now, songket has been oriented to life necessities. (2) the income of songket entrepreneurs is relatively high, and the workers are relatively low. There is a disparity of income between employers and workers, (3) As a solution to overcome income disparities between employers and Palembang songket workers, researchers offer a harmonious wage theory which is a combination of Islamic and Malay wage system, (4) work ethic of Palembang songket workers is diligent, diligent and resilient, not lazy. Penelitian ini berjudul “Upah Dan Etos Kerja Pada Kasus Usaha Songket Palembang Dalam Perspektif Islam Dan Melayu”, (1) gambaran umum usaha songket Palembang pada masa Sriwijaya dan Kesultanan kerajinan songket belum menjadi komoditi bernilai ekonomis, sejak kemerdekaan sampai sekarang, songket telah berorientasi pada kebutuhan hidup. (2) pendapatan para pengusaha songket relatif tinggi, dan para pekerja relatif rendah. Terjadi disparitas pendapatan antara pengusaha dan pekerja, (3) Sebagai solusi mengatasi disparitas pendapatan antara pengusaha dan pekerja songket Palembang, Peneliti menawarkan teori upah harmonis yang merupakan gabungan sistem upah Islam dan Melayu, (4) etos kerja para pekerja songket Palembang adalah rajin, tekun dan ulet, bukan pemalas.